2006
DOI: 10.1080/13854040590967144
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of MMPI-2 Validity Scales and Indicators to Malingered Neurocognitive Dysfunction in Traumatic Brain Injury

Abstract: The present study used a known-groups design to determine the classification accuracy of 10 MMPI-2 validity scales and indicators in the detection of cognitive malingering in traumatic brain injury. Participants were 259 traumatic brain injury and 133 general clinical patients seen for neuropsychological evaluation. The TBI patients were subdivided into groups based on a comprehensive examination of effort following Slick, Sherman, and Iverson's (1999) criteria. More extreme scores demonstrated excellent speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 31 publications
(36 reference statements)
2
54
0
Order By: Relevance
“…This supports previous research which has found the MMPI-2 version of this scale to be sensitive to MND and MPRD (Bianchini et al 2008;Greve et al 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This supports previous research which has found the MMPI-2 version of this scale to be sensitive to MND and MPRD (Bianchini et al 2008;Greve et al 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Due to the small size of the definite malingering group, the probable (n=70) and definite (n=21) groups were combined and a probable/definite (n=91) group was used for the MANOVA in relation to the possible malingering and incentive-only groups. Combination of these groups has been utilized in previous studies (see Curtis et al 2006;Greve et al 2006Greve et al , 2009Larrabee 2003). We conducted a one-way MANOVA to determine whether there were overall differences on the MMPI-2-RF validity scales across the three groups.…”
Section: Differential Symptom Presentationmentioning
confidence: 99%
“…We depended on the clinical impression of neuropsychologists interpreting the neuropsychological test battery [46][47], the WAIS-III and WMS-III [50][51][52][53], the CVLT-II [55][56], the Test of Memory Malingering [57][58], the WMS-III [52], and the MMPI-II [59]. While the pattern of findings on neuropsychological testing may suggest TBI, neuropsychological testing is not diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary memory and learning ability were evaluated with the third edition of the Wechsler Memory Scale (WMS-III) [49][50][51][52][53], the full version of the second edition of the California Verbal Learning Test (CVLT-II) [54][55][56], and the Rey Complex Figure Test. The likelihood that the responses given on neuropsychological testing were sincere and that the subjects were applying a good effort was assessed by interpretation of performance on several tests, including the Test of Memory Malingering [57][58], the WMS-III [52][53], and the MMPI-II [59]. Depression was assessed with the second edition of the Beck Depression Inventory [60].…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…The MMPI-2 has been examined in relation to the various potential forms of response bias, including feigned emotional distress (Crawford, Greene, Dupart, Bongar, & Childs, 2006), including PTSD (discussed later in details), as well as criteria for Malingered Neurocognitive Dysfunction (MND; Slick, Sherman, & Iverson, 1999) and Malingered Pain-Related Disability (MPRD; Bianchini, Greve, & Glynn, 2005). Greve, Bianchini, Love, Brennan, and Heinly (2006) examined the MMPI-2 validity scales in a sample of traumatic brain injury and general clinical neuropsychological patients. These authors found that the MMPI-2 validity scales (particularly FBS and F B ) exhibited good classification in discriminating MND from non-malingering patients.…”
Section: Mmpi-2 and Psychological Injury And Related Evaluationsmentioning
confidence: 99%